Determining the spectral transmittance of photochromic contact lenses. Issue 5 (October 2021) - Alabi, Emmanuel B.; Simpson, Trefford L.; Harris, Tyler; Whitten, Keith
Abstract: Purpose: This study evaluates the spectral transmission of photochromic contact lenses. Method: A custom built photochromic filter transmission testing device (ICS photochromic bench) was developed to measure the spectral transmission of light adaptive filters. The spectral properties of seven contact lenses were measured using the ICS photochromic bench at 23⁰C and 35⁰C in their exposed (darkening) state at time points 0 s, 45 s, 90 s, and 15 min. and their unexposed (fading) state at 45 s, 15 min. and 20 min.. Mixed between and within repeated measures ANOVA (MRM-ANOVAs) and generalized additive modeling (GAMs) were used to compare the effects of temperature and solar exposure time on spectral transmittance of photochromic contact lenses. Results: The mean (±SD) transmission of photochromic contact lenses in the exposed state were 94.7 ± 0.2, 39.1 ± 1.4, 27.0 ± 0.7 and 14.7 ± 1.0, and 93.7 ± 0.9, 38.8 ± 2.4, 30.2 ± 1.8, and 26.1 ± 1.0 at times 0 s, 45 s, 90 s, and 15 min. at 23⁰C and 35⁰C respectively. The mean (±SD) transmission of photochromic contact lenses in the unexposed state were 18.3 ± 1.5, 71.3 ± 2.4, and 80.2 ± 2.4, and 39.1 ± 1.0, 90.6 ± 1.0 and 91.1 ± 0.9 at times 45 s, 15 min. and 20 min. at 23⁰C and 35⁰C respectively. There was a significant decrease in light transmission as solar exposure time increased (GAM, MRM-ANOVA, p < 0.05 ). There was a significant effect of temperature and solar exposure time on the photochromic contact lenses (GAM, MRM-ANOVA, p < 0.05 ) . The differences in the light transmitted by the photochromic contact lenses occurred at time 90 s and 15 min (Tukey HSD, at 90 s and 15 min, p < 0.05), where contact lenses at a temperature of 35⁰C showed greater light transmission than that at 23⁰C. There were differences in spectral transmittance based on the temperature of the contact lens. Contact lenses at 35⁰C transmitted more light than at 23⁰C at all unexposed times (MRM-ANOVA, p < 0.05). Conclusion: Spectral transmission of photochromic contact lenses were successfully measured with the ICS photochromic bench. Temperature appears to influence both the activation and deactivation of photochromic contact lenses such that the higher the temperature, the greater the light transmission.